The relationship between foreign direct investment and economic growth in Iraq after 2003(reality and ambition) - جاسم محمد سلمان (Journal of Economics and Administrative Sciences, 2017)
Foreign direct investment is considered one of important bases to blind economy for many. Countries as if the main stage for developing national economy ,so for this ,many of countries give great prominence to the role of drivel foreign investment due to its importance as one of economic growth pillars in the developing countries. They offer a support for modern technology, organizational and managerial skills. Dneto the importance of direct foreign investment on the economic growth, today, we discover that Iraq in need to rebnlid the in frastructuve and renew what has been destroyed during was in many production and export institutions . as well as the internal and external challenges which Iraq faced like the huge financial wasting results from the corvnption of many Iraq officals and that led to prevent Iraq from allocating these funds in developing projects which contributing in raising the growth rate in the economic sectors and the political influences by neighboring countries and this often reflecting negatively on all local levels , as long as Iraq seeking to enconvaqe it’s activities so direct foreign investment plays a gruel role to increase the economic growth rates . Iraq, nowadays real:zes that investment needs suitable environment to attract foreign investment through putting legal protection. We have reached two important conclusions. The first is that foreign direct investment flows in Iraq after 2003 have increased due to the lifting of the economic sanctions imposed on Iraq, the openness of Iraq to the outside world and the issuance of the Investment Law for 2006, but these flows are still modest and weak and the majority of them In the oil sector, with regard to the second conclusion that security and political instability and cases of administrative and financial corruption were among the reasons that prevented the provision of an appropriate investment atmosphere capable of attracting foreign investment.